Factors affecting prognosis in high-intermediate risk endometrial cancer in according to ESMO/ESGO/ESTRO risk classification – FIGO 2023 analysis of survival outcomes and staging dynamics compared to the FIGO 2009 system - Guleryuz, Eren Can; Korpe, Busra; Korkmaz, Vakkas (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Accurate staging is essential for determining treatment strategies and predicting outcomes in endometrial cancer (EC). The FIGO staging system was updated in 2023 to incorporate histological and molecular features. This study evaluates the impact of the FIGO 2023 system on high-intermediate risk endometrioid EC cases and compares its prognostic value with the FIGO 2009 system. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Material and methods. A retrospective analysis of 140 high-intermediate risk endometrial cancer cases from two tertiary hospitals was conducted. Patients were reclassified using FIGO 2023, and staging shifts were analyzed. Survival outcomes, including overall survival (OS) and progression-free survival (PFS), were assessed using Kaplan-Meier analysis and log-rank tests. Univariate and multivariate regression analyses were performed to identify prognostic factors. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Results. Within this high-intermediate risk group, patients were stratified into three groups: group 1 (n=79) consisted of those with LVSI (+) Stage I, group 2 (n=17) included patients with LVSI (-) Stage IB grade 3, and group 3 (n=44) comprised individuals with Stage II. Based on age, a statistically significant difference was identified between group 1 and group 3 (p<0.05), while no statistically significant difference in BMI was observed among the groups (p>0.05). Additionally, there was a statistically significant difference among the groups concerning the type of surgery performed (p<0.05) Although no statistically significant difference in survival outcomes was observed, a trend toward improved risk stratification in OS was noted. Positive lymphovascular space invasion emerged as a key factor influencing upstaging. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Conclusion. FIGO 2023 provides a refined staging approach that better aligns with clinical outcomes. Larger prospective studies incorporating molecular profiling are needed to confirm its prognostic utility.